Extending autologous transplantation as first line therapy in multiple myeloma patients with severe renal impairment: a retrospective study by the SFGM-TC. (June 2018) - Augeul-Meunier, Karine; Chretien, Marie-Lorraine; Stoppa, Anne-Marie; Karlin, Lionel; Benboubker, Lofti; Diaz, Jose; Mohty, Mohamad; Yakoub-Agha, Ibrahim; Bay, Jacques-Olivier; Perrot, Aurore; Bulabois, Claude-Eric; Huynh, Anne; et al.
Abstract Renal impairment is a common complication of multiple myeloma (MM), accounting for 20–30% of MM patients at diagnosis and 40–50% of patients during the course of their disease. This feature is associated with poor prognosis and shorter survival as compared to patients with normal renal function (NRF). Therefore, therapeutic management is challenging as autologous stem cell transplantation (ASCT) is often not considered as a valuable strategy, mainly due to concerns of toxicity. In this retrospective and multicenter study, we included 55 MM patients with dialysis-dependent or independent renal failure who underwent high-dose melphalan-based ASCT in order to assess the efficacy outcomes and toxicities of this strategy. Response to ASCT was at least VGPR (very good PR) in 58% of patients and 96% of patients who also received bortezomib-based induction were at least in PR after ASCT. Median OS was 76 months and median PFS was 55 months, similarly to MM patients with NRF. In multivariate analysis, dose of melphalan (140 mg/m2 ) was correlated with better PFS (18 months, P  = 0.005). Toxicities included febrile neutropenia (75%) and severe mucositis (34%). Overall, this work confirmed that ASCT conditioned by 140 mg/m2 melphalan is a beneficial procedure for MM patients with renal failure.